Encaged-anion tunable luminescence of Ce3 +-activated single host Ca12Al14O32Cl2 phosphor for UV pumped multi-color LEDs. (5th October 2016) - Liu, Xiuling; Liu, Yuxue; Yan, Duanting; Zhang, Meng; Yang, Jian; Zhu, Hancheng; Liu, Chunguang; Xu, Changshan; Wang, Xiaojun
Abstract: A novel tunable-light-emitting single-host Ca12 Al14 O32 Cl2 :0.5%Ce 3 + phosphor has been prepared in H2 atmosphere by a solid-state reaction method. Upon 340 nm excitation, the phosphor shows an asymmetric broadband emission centered at 503 nm, assigned to the 5d - 4f transitions of Ce 3 + . For Ce 3 + doped Ca12 Al14 O32 Cl2, a large red-shift (~ 69 nm) and an increased full width at half maximum from 66 to 115 nm can be observed in comparison with that of the Ce 3 + doped Ca12 Al14 O33 sample. In particular, the emission color of the Ca12 Al14 O32 Cl2 :0.5%Ce 3 + phosphor can be tuned from blue to yellow by controlling anions in the nanocages, causing the different lattice deformations. Moreover, the CIE coordinates of the Ca12 Al14 O32 Cl2 :0.5%Ce 3 + phosphor move from yellow to blue as the heating temperature increases from 293 to 623 K. Our results suggest that the encaged-anion modulation in combination with the heating is an effective strategy for realizing highly color tunable emission of Ce 3 + doped in a single host, and furthermore, for designing novel phosphors for UV pumped multi-color LEDs and related devices. Graphical abstract: Highlights: A novel tunable-light-emitting single-host Ca12 Al14 O32 Cl2 :0.5%Ce 3 + phosphor has been prepared in H2 atmosphere. A large red-shift (from 434 to 503 nm) and an increased full width at half maximum can be observed. The emission of Ce 3 + is tuned simply by controlling anions (O 2 −, Cl − ) in the nanocages. The CIE coordinates of the phosphor move from yellow to blue by increasing temperature from 293 to 623 K.